Optimal Planning of Nurses’ Redeployment at Patient Overflow, ISSN / ISBN 978-94-62520-74-5 / 2352-538X - Bellala Djamel (Proceedings of the 2015 AASRI International Conference on Circuits and Systems, 2015)
In order to provide to his patients a quality medical service at lower cost, the General Administration Department of a University Hospital wants to maintain the number of the allocated nurses as low as possible while guaranteeing a satisfying level of health care. The nurses’ redeployment is an optimization problem that falls under the category of integer linear programming problems whose graphical model is a digraph. The mathematical model is composed of an objective function of several interdependent variables to be obtained and some equality and side constraints that the General Administration Department should not violate in order to achieve satisfaction. The solution of this kind of problems rests on the use of an iterative method known as the simplex algorithm.